2011
DOI: 10.5251/abjna.2011.2.4.630.637
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amodiaquine on oestrus cycle, ovarian histology and oxidative stress makers in regular cyclic sprague-dawley rats

Abstract: This study investigated the effect of Amodiaquine hydrochloride (AQ.HCl) administered by gavage on the oestrous cycle, ovarian morphology and on the antioxidant status of superoxide dismutase (SOD) and catalase (CAT) in the ovary of 15 regular cyclic Sprague-Dawley rats. The experiment was divided into 3 groups as follows: group I-received 6 mg/kg bw AQ.HCl for 28 day; group II-received 12 mg/kg bw of AQ.HCl for 28 days; and group III-received distilled water and served as control. The animals were autopsied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The report of this study is in agreement with Osinubi et al,25 who reported that quinine significantly increased levels of MDA in the testes. Also, in another study using amodiaquine, it was reported that amodiaquine caused a significant reduction in the enzymatic anti-oxidant activities of SOD and catalase in the ovaries of Sprague-Dawley rats13. An imbalance between ROS production and anti-oxidants results in oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The report of this study is in agreement with Osinubi et al,25 who reported that quinine significantly increased levels of MDA in the testes. Also, in another study using amodiaquine, it was reported that amodiaquine caused a significant reduction in the enzymatic anti-oxidant activities of SOD and catalase in the ovaries of Sprague-Dawley rats13. An imbalance between ROS production and anti-oxidants results in oxidative stress.…”
Section: Discussionmentioning
confidence: 97%
“…Quinine was administered daily for 28 days by gavage13. At the end of the treatment period, the rats were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%